2009
DOI: 10.1186/2047-783x-14-3-106
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical exercise on plasma levels of relaxin, NTproANP, and NTproBNP in patients with ischemic heart disease

Abstract: The insulin-like and vasodilatatory polypeptide relaxin (RLX), formerly known as a pregnancy hormone, has gained interest as a potential humoral mediator in human heart failure. Controversy exists about the relation between plasma levels of RLX and the severity of heart failure. The present study was designed to determine the course of RLX, atrial, and brain natriuretic peptide (NT-proANP and NT-proBNP) during physical exercise in patients with ischemic heart disease (IHD) and to relate hormone levels to peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
(28 reference statements)
2
10
1
Order By: Relevance
“…Although previous studies have indicated that changes in the serum RLX-2 are involved in the pathogenesis of CVDs, 28,29) our study did not support that the serum level of RLX-2 were different among those with or without UA in the normal blood glucose patients. Moreover, the serum levels of RLX-2 were not associated with the severity of the coronary lesions in UA patients with glucose metabolism dysfunction.…”
contrasting
confidence: 55%
“…Although previous studies have indicated that changes in the serum RLX-2 are involved in the pathogenesis of CVDs, 28,29) our study did not support that the serum level of RLX-2 were different among those with or without UA in the normal blood glucose patients. Moreover, the serum levels of RLX-2 were not associated with the severity of the coronary lesions in UA patients with glucose metabolism dysfunction.…”
contrasting
confidence: 55%
“…Increased circulating relaxin levels in human heart failure were not confirmed in two subsequent clinical studies (Kupari et al, 2005;Heringlake et al, 2009), possibly due to a methodological issue related to the utilization of a new batch of antiserum (Kupari et al, 2005;Heringlake et al, 2009) for the ELISA (Dschietzig et al, 2001b;Fisher et al, 2002). Increased relaxin gene expression in chronic heart failure was confirmed by two independent studies using the rat infarction model Zhang et al, 2005).…”
Section: Physiologic Roles Of Relaxin Family Peptide Receptors Andmentioning
confidence: 70%
“…11 The interassay coefficient of variation was 9.3% at 130 pg/ml and 14.4% at 3,890 pg/ml. The lower detection limit was 5 pg/ml.…”
Section: Determination Of High-sensitivity Troponin T and N-terminal mentioning
confidence: 98%
“…The subgroup of high-risk patients with a EuroSCORE greater than 10 consisted of 102 patients with a median additive EuroSCORE of 12 (11)(12)(13)(14). The patients in this group were older (74 yr [67-78 yr]), weighed less (75 kg [67-97 kg]), and were smaller (170 cm [160 -178 cm]; all: P Ͻ 0.05) compared with the total cohort.…”
Section: Statistical Analysesmentioning
confidence: 99%